Content management for distance learning program: A case study on a distance learning program in Thailand - Chan, Sow Hup (2004)
Institutions are considering distance learning to meet the ever expanding needs of students in many parts of the world.Due to the lack of face-to-face contact with teachers and peers, the emphasis on content management is vital to assure positive learning. The purpose of this paper is to derive lessons learned from the findings of a case study on a distance learning English Language program, and to highlight the impact of what can possibly happen when content management seemed to be nonexistent.The paper will provide some practical suggestions for educators considering course content management.The importance of evaluation and benchmarking in knowledge sharing is stressed. Much knowledge can be gained from such effort. Proactive measures taken can enhance the institution’s reputation.